2022
DOI: 10.24875/j.gamo.22000208
|View full text |Cite
|
Sign up to set email alerts
|

Tumores primarios de alto grado del sistema nervioso central: análisis clínico y epidemiológico de la experiencia de un centro

Abstract: Background: Epidemiological data on the clinical presentation of high-grade primary tumors, the most common histological variables and prevalence, and sociodemographic variables were addressed from January 2016 to December 2020. Method: The sample was calculated from the primary tumors provided by the statistics department, determined the ICD-10 (C-71), finding 105. Results: 114 cases of high-grade primary tumors, most of them men; glioblastoma was the most common variant, followed by medulloblastoma. The fron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
0
1
Order By: Relevance
“…However, compared to previous studies, it draws our attention that mortality [32][33][34] is maintained and with a tendency to decrease as a result of the implementation of new therapeutic regimens [35][36][37] included in those considered to present better outcomes for patients who undergo some type of radiotherapy in combination with new surgical approaches within which it is suggested that they be minimally invasive and before performing the procedure, they are also accompanied by very good interdisciplinary planning. On the other hand, a higher incidence of meningiomas had been described [38][39][40], however, it was able to denote that although it continues to be high in our study, it was surpassed by tumors derived from glia [41][42][43]. The most frequent location of brain tumors, in what was show, is the anterior fossa, wherein gliomas and meningiomas are most frequently seen.…”
Section: Discussioncontrasting
confidence: 47%
“…However, compared to previous studies, it draws our attention that mortality [32][33][34] is maintained and with a tendency to decrease as a result of the implementation of new therapeutic regimens [35][36][37] included in those considered to present better outcomes for patients who undergo some type of radiotherapy in combination with new surgical approaches within which it is suggested that they be minimally invasive and before performing the procedure, they are also accompanied by very good interdisciplinary planning. On the other hand, a higher incidence of meningiomas had been described [38][39][40], however, it was able to denote that although it continues to be high in our study, it was surpassed by tumors derived from glia [41][42][43]. The most frequent location of brain tumors, in what was show, is the anterior fossa, wherein gliomas and meningiomas are most frequently seen.…”
Section: Discussioncontrasting
confidence: 47%